Analysis of the Influence of Brand Image, Reference Group, Location on Purchases at Warkop On Mada Rantauprapat - Samuel Rianto; Elida F.S. Simanjorang; Eva Fitria (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
The purpose of this research is to analyze the effect of brand image, reference group, location on purchases at Warkop On Mada Rantauprapat. The population in this study are customers or buyers at the On Mada Rantauprapat coffee shop. The sample collection technique used is probability sampling by leading to random sampling incidents, the number of samples used is 100 buyers or consumers at the On Mada Rantauprapat coffee shop. The research resulted in the conclusion that the reference group variable and location variable had an impact independently or partially on the purchasing decision variable at the On Mada Rantauprapat coffee shop where the t-count value was greater than the t table for each variable and was supported by a Sig value less than 0.05 for each -Each variable, while the variable brand image does not affect independently or partially on the purchasing decision variable seen from the t count is smaller than t table and the Sig value is greater than 0.05. Based on the results of the f test, it can be concluded that the brand image, reference group and location have a simultaneous impact on purchasing decisions in terms of Sig <0.05 and based on the value of f count 27.323 is greater than f table 2.698. Based on the R-Square value of 0.679, the value of the contribution of brand image, reference group and location variables is 67.9% of the purchase decision